Development of Mouthwash from Guava Leaf Extract and Maweng Kruea Fruit Extract - Manud, Thanyaphat; Fakkham, Charinthorn; Thumpad, Anongnooch; Phio-on, Kanokkorn (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2024)
This study aims to test the antibacterial efficacy and antioxidant activity of leaf extract and Maweng Kruea fruit extract and develop a mouthwash product containing extracts from guava leaf and Maweng Kruea. The experiments were conducted by extracting both herbs with 95 % ethanol. Research results indicated that herbal extracts possess inhibitory effects against Streptococcus mutans. The minimum inhibitory concentration (MIC) that can inhibit microbial growth was found at 0.25 mg/mL, while the minimum bactericidal concentration (MBC) for killing bacteria was found at 0.25 mg/mL, with an MBC/MIC ratio of 1. The mouthwash composed of guava leaf and Maweng kruea fruit extracts exhibited antioxidant properties with an IC50 of 16.06 μL/ml. The developed mouthwash from these herbal extracts was found to have physical properties suitable for oral use, including a clear yellow color, slightly bitter and slightly sweet taste, minty aroma, slight cooling sensation, no tongue irritation, and a pH value of 6.7, making it suitable for oral conditions.